Worlds Next Door: A Candidate Giant Planet Imaged in the Habitable Zone of α Centauri A. I. Observations, Orbital and Physical Properties, and Exozodi Upper Limits - Charles Beichman; Aniket Sanghi; Dimitri Mawet; Pierre Kervella; Kevin Wagner; Billy Quarles; Jack J. Lissauer; Max Sommer; Mark Wyatt; Nicolas Godoy; William O. Balmer; Laurent Pueyo; et al. (The Astrophysical Journal Letters)
We report on coronagraphic observations of the nearest solar-type star, α Centauri A ( α Cen A), using the MIRI instrument on the James Webb Space Telescope. The proximity of α Cen (1.33 pc) means that the star’s habitable zone is spatially resolved at mid-infrared wavelengths, so sufficiently large planets or quantities of exozodiacal dust would be detectable via direct imaging. With three epochs of observation (2024 August, 2025 February, and 2025 April), we achieve a sensitivity sufficient to detect T _eff  ≈ 225–250 K (1–1.2 R _Jup ) planets between 1″–2″ and exozodiacal dust emission at the level of >5–8× the brightness of our own zodiacal cloud. The lack of exozodiacal dust emission sets an unprecedented limit of a few times the brightness of our own zodiacal cloud—a factor of ≳10 more sensitive than measured toward any other stellar system to date. In 2024 August, we detected an F _ν (15.5 μ m) = 3.5 mJy point source, called S 1, at a separation of 1 $\mathop{.}\limits^{\unicode{x02033}}$ 5 from α Cen A at a contrast level of 5.5 × 10 ^−5 . Because the 2024 August epoch had only one successful observation at a single roll angle, it is not possible to unambiguously confirm S 1 as a bona fide planet. Our analysis confirms that S 1 is neither a background nor a foreground object. S 1 is not recovered in the 2025 February and April epochs. However, if S 1 is the counterpart of the object C 1, seen by the Very Large Telescope/New Earths in Alpha Centauri Region program in 2019, we find that there is a 52% chance that the S 1 +  C 1 candidate was missed in both follow-up JWST/MIRI observations due to orbital motion. Incorporating constraints from the nondetections, we obtain families of dynamically stable orbits for S 1 +  C 1 with periods between 2 and 3 yr. These suggest that the planet candidate is on an eccentric ( e  ≈ 0.4) orbit significantly inclined with respect to the α Cen AB orbital plane ( i _mutual  ≈ 50 ^∘ , prograde, or ≈130 ^∘ , retrograde). Based on the photometry and inferred orbital properties, the planet candidate could have a temperature of 225 K, a radius of ≈1–1.1 R _Jup , and a mass between 90 and 150 M _⊕ , consistent with radial velocity limits. This Letter is first in a series of two papers: Paper II discusses the data reduction strategy and finds that S 1 is robust as a planet candidate, as opposed to an image or detector artifact.